(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
his article examines the forms of land ownership and the tax system in the Bukhara Emirate during the second half of the 18th century and the 19th century, focusing on the legal and economic characteristics of amlok (state), mulk (private), and waqf (religious) lands. Based on the works of A.A. Semyonov, M.A. Abdurahimov, K.M.